PENGARUH COMPUTER KNOWLEDGE DAN COMPUTER SELF-EFFICACY TERHADAP EFEKTIVITAS SISTEM KEUANGAN DESA DI KABUPATEN BOMBANA - Yusuf, Muh. Fathir Maulid; Sari, Ika Maya; Garusu, Ilham Akbar; Rauf, Dian Mayafaty (SINERGI : Jurnal Riset Ilmiah, 2024)
This study aims to examine the effect of computer knowledge and computer self-efficacy on the effectiveness of village financial systems in Bombana district. The data used in this research is quantitative data, the data source used is primary data, namely data obtained directly from the research location in the form of raw data in the form of a questionnaire or questionnaire and data in the form of additional information through interviews. The data was analysed using multiple linear regression analysis techniques, the purpose of which is to determine the effect of the relationship between the independent variable and the dependent variable in this study. The results showed that partially computer knowledge and computer self-efficacy had a significant effect on the effectiveness of the financial system, each of which was 0.481 and 0.510 with a significance of 0.001 each. Likewise, with simultaneous testing that computer knowledge and computer self-efficacy affect the effectiveness of village financial systems in Bombana district. This means, if computer knowledge and computer self-efficacy are getting better, the effectiveness of the financial system will also increase. So that the effectiveness of the village financial system in Bombana district will run effectively.